SELLING PRICE DETERMINATION MODEL WITH TIME DRIVEN ACTIVITY BASED COSTING METHOD AT UMKM ”SALE PISANG” IN BANYUWANGI REGENCY - Deddy Kurniawansyah (Berkala Akuntansi dan Keuangan Indonesia, 2021)
The purpose of this study to examine (1) how the stages of the production process for “Sale Pisang Product’ that affects the determination of the selling price of Micro, Small, and Medium Enterprises in Banyuwangi? (2) How is the selling price computing model "Banana Sale Products" able to determine a competitive selling price for Micro, Small and Medium Enterprises in Banyuwangi?. This Study used survey, qualitative exploratory and action. The analysis data used triangulation method. The results obtained in this studi is the process of computing the production cost of “Sale Pisang Product” still uses a traditional method, so that the resulting product cost is distorted and the selling price becomes uncompetitive. In fact, the product cost compute model using Time Driven Activity Based Costing provides more accurate and informative information for Micro, Small and Medium Enterprises actors in making decisions such as determining the selling price. The Time Driven Activity Based Costing method is able to reduce costs and increase the net income of each “sale pisang” variant. The contribution of this study is expected to create competitive selling price of “Sale Pisang Product” and improve the economic competitiveness of Kab. Banyuwangi is more dynamic based on the potential of natural resources and local wisdom.